LRRK2 variation and dementia with Lewy bodies. (October 2016) - Heckman, Michael G.; Soto-Ortolaza, Alexandra I.; Sanchez Contreras, Monica Y.; Murray, Melissa E.; Pedraza, Otto; Diehl, Nancy N.; Walton, Ronald; Labbé, Catherine; Lorenzo-Betancor, Oswaldo; Uitti, Ryan J.; van Gerpen, Jay; Ertekin-Taner, Nilüfer; et al.
Abstract: Introduction: The leucine-rich repeat kinase 2 ( LRRK2 ) gene contains several variants that cause Parkinson's disease (PD) and others that modify PD risk. However, little is known about the role of LRRK2 in dementia with Lewy bodies (DLB). Aims of this study were to screen DLB patients for pathogenic LRRK2 variants and to evaluate associations between common LRRK2 variants and risk of DLB. Methods: 417 clinical DLB patients and 1790 controls were included in the primary analysis. Additionally, 355 Lewy body disease patients assessed as having a high likelihood of clinical DLB based on neuropathological findings were included in secondary analysis. Seven pathogenic LRRK2 variants were assessed in patients, while 17 common LRRK2 exonic variants and 1 GWAS-nominated common LRRK2 PD-risk variant were evaluated for association with DLB. Results: We identified carriers of 2 different pathogenic LRRK2 variants. One clinical DLB patient was a p.G2019S carrier, while in the pathological high likelihood DLB series there was one carrier of the p.R1441C mutation. However, examination of clinical records revealed the p.R1441C carrier to have PD with dementia. Evaluation of common variants did not reveal any associations with DLB risk after multiple testing adjustment. However, a non-significant trend similar to that previously reported for PD was observed for the protective p.N551K-R1398H-K1423K haplotype in the clinical DLB series (OR: 0.76, P = 0.061). Conclusion: LRRK2 does not appear to play a major role in DLB, however further study of p.G2019S and the p.N551K-R1398H-K1423K haplotype is warranted to better understand their involvement in determining DLB risk. Highlights: We studied 417 DLB patients and 1790 controls in our primary analysis. 7 pathogenic LRRK2 variants and 18 common LRRK2 variants were assessed. We identified 1 DLB patient who was a carrier of the LRRK2 p.G2019S mutation. The p.N551K-R1398H-K1423K haplotype showed a non-significant trend toward a protective association with DLB risk. These findings suggest that LRRK2 variation may play a limited role in susceptibility to DLB.